Genes From a Translational Analysis Support a Multifactorial Nature of White Matter Hyperintensities. Issue 2 (February 2015) - Lopez, Lorna M.; Hill, W. David; Harris, Sarah E.; Valdes Hernandez, Maria; Munoz Maniega, Susana; Bastin, Mark E.; Bailey, Emma; Smith, Colin; McBride, Martin; McClure, John; Graham, Delyth; Dominiczak, Anna; et al.
Abstract : Background and Purpose—: White matter hyperintensities (WMH) of presumed vascular origin increase the risk of stroke and dementia. Despite strong WMH heritability, few gene associations have been identified. Relevant experimental models may be informative. Methods—: We tested the associations between genes that were differentially expressed in brains of young spontaneously hypertensive stroke–prone rats and human WMH (using volume and visual score) in 621 subjects from the Lothian Birth Cohort 1936 (LBC1936). We then attempted replication in 9361 subjects from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE). We also tested the subjects from LBC1936 for previous genome-wide WMH associations found in subjects from CHARGE. Results—: Of 126 spontaneously hypertensive stroke–prone rat genes, 10 were nominally associated with WMH volume or score in subjects from LBC1936, of which 5 ( AFP, ALB, GNAI1, RBM8a, and MRPL18 ) were associated with both WMH volume and score ( P <0.05); 2 of the 10 ( XPNPEP1, P =6.7×10 −5 ; FARP1, P =0.024) plus another spontaneously hypertensive stroke–prone rat gene ( USMG5, P =0.00014), on chromosomes 10, 13, and 10 respectively, were associated with WMH in subjects from CHARGE. Gene set enrichment showed significant associations for downregulated spontaneously hypertensive stroke–prone rat genes with WMH in humans. In subjects from LBC1936, we replicated CHARGE's genome-wide WMH associations on chromosomes 17 ( TRIM65 and TRIM47 ) and, for the first time, 1 ( PMF1 ). Conclusions—: Despite not passing multiple testing thresholds individually, these genes collectively are relevant to known WMH associations, proposed WMH mechanisms, or dementia: associations with Alzheimer's disease, late-life depression, ATP production, osmotic regulation, neurodevelopmental abnormalities, and cognitive impairment. If replicated further, they suggest a multifactorial nature for WMH and argue for more consideration of vascular contributions to dementia. Abstract : Supplemental Digital Content is available in the text.